Role of fine-needle aspiration cytology in peripartum/pregnancy-associated breast malignancy - Six cases with review of literature - Priyadarshini Dehuri; Debasis Gochhait; Durga Devi (Wolters Kluwer Medknow Publications, 2020)
Background: The incidence of pregnancy associated breast cancers is on the rising trend in different parts of the world. There are occasional studies dealing with the fine needle aspiration cytology (FNAC) and clinicopathological characteristics of these tumors. Objectives: To study the cytomorphology and clinicopathological characteristics of pregnancy associated breast cancers and review the existing literature on the pathological characteristics. Methods: This is a retrospective study which includes cases of breast cancer which were diagnosed during peripartum period. FNAC was performed for all the cases from primary and metastatic sites along with correlation of the clinicopathological characteristics. Results: In the study group, 4 cases were lactating at the time of diagnosis, 1 patient presented at 37 weeks of her pregnancy and another patient presented 1 week after ruptured tubal ectopic pregnancy. Histologically two cases of infiltrating duct carcinoma -not otherwise specified (IDC-NOS), one case of invasive duct carcinoma with mucinous differentiation, one case of invasive duct carcinoma with concomitant lactating adenoma and one case each of metaplastic carcinoma and malignant phyllodes tumor. Only a single case was found to be positive for both the estrogen and progesterone receptors and another case only for estrogen receptors. None of the cases were found to positive for Her -2 neu. Conclusion: FNAC still serves as a reliable diagnostic measure inspite of the close mimics, especially when combined with cell block preparation. Further documentation of the clinicopathological features is essential for establishing the prognostic parameters and treatment guidelines for these peripartum breast cancers.